Climate and satellite indicators to forecast Rift Valley fever epidemics in Kenya - Linthicum, K.J; Anyamba, A; Tucker, C.J; Kelley, P.W; Myers, M.F; Peters, C.J (Science (American Association for the Advancement of Science), 1999)
All known Rift Valley fever virus outbreaks in East Africa from 1950 to May 1998, and probably earlier, followed periods of abnormally high rainfall. Analysis of this record and Pacific and Indian Ocean sea surface temperature anomalies, coupled with satellite normalized difference vegetation index data, shows that prediction of Rift Valley fever outbreaks may be made up to 5 months in advance of outbreaks in East Africa. Concurrent near-real-time monitoring with satellite normalized difference vegetation data may identify actual affected areas.